(untitled) (Asian Journal of Pharmaceutics (AJP), 2022)
Tablets are the most widely used formulation amidst all dosage forms as its convenient to intake, offer precise dosing and, have low cost. Functionally, compressed tablets can be categorized into simply compressed tablets, coated and multiple compressed tablets. Further, multiple compressed tablets can be classified as layered tablets and tablet in tablet dosage form. Among these, tablet in tablet technology is an innovative and pragmatic approach, where a tablet is compressed with a core tablet in the center. Moreover, the inlay tablet is also a form of tablet in tablet where the top surface of the core tablet is completely exposed within the outer tablet. tablet in tablet technology offers various advantages over conventionally coated tablet formulations. There is, no water penetration into the core tablet hence, no core softening occurs, no seal coat is required over the core tablet. Incompatible API’s can be formulated into a single tablet by physically separating them. Drug deterioration can be curtailed down by incorporating sensitive API into a core tablet, thus preventing environmental degradation. It also prevents drug degradation in the gastric environment, helpful in concealing the bitter and unpleasant taste of the drug, despite this, the technology has some minor disadvantages like improper centration which may cause fragile edges, and low-density drug substances in the core may lead to inappropriate formulation size. There are certain considerations to be taken while developing formulation in tablet in tablet dosage form. Ideally, the weight of outer tablet granules must be kept twice in weight to that of a core tablet. The core tablet must be kept as small as possible. The outer tablet granules must possess cohesiveness and plasticity to produce a physically stable formulation. There are various Machines available to manufacture tablet in tablet formulation, namely, the Colton Model 232 and the Strokes model 538, Manesty Drycota, etc. There are many formulations developed as well as approved patents using tablet in tablet technology whereby it replaces conventional coating techniques, overcoming incompatibility, and stability issues. This review is an attempt to congregate and present meaningful insight to this revolutionary technology.